Impact of Dexmedetomidine on Bupivacaine in ultrasound-guided supraclavicular brachial plexus block in forearm surgeries - Mubina Begum Bijapur; Nazeer Ahmed Kudligi; Sanjeev B; Shaik Asma; Ganga Sankangoudar (Al Ameen Medical College, 2019)
Background and Aims: Many adjuvants have been used with local anesthetics to enhance the analgesic duration of brachial plexus block. Our study aimed to evaluate the effect of Dexmedetomidine as an adjuvant to Bupivacaine in USG-guided supraclavicular Brachial plexus block (BPB). Methods: A randomized double-blinded study carried on 60 patients with ASA physical status I and 2, undergoing forearm surgeries. In group B, Bupivacaine 0.5% 2mg/kg administered and in group BD, patients were administered 2mg/kg of Bupivacaine 0.5% with Dexmedetomidine 1 µg/kg under ultrasound-guided supraclavicular BPB. The onset of sensory and motor blockade as well as duration of analgesia was recorded. The VAS score was noted before block, just after block, and then every 5 minutes until initial 20 minutes thereafter every half hour till first 24 hours. The time to first rescue analgesic, total analgesic consumption, side effects, and haemodynamic variables were recorded. Result: Dexmedetomidine group showed, statistically significant prolonged analgesia, delayed time for first rescue analgesic demand and less analgesic consumption in first 24 hours post- surgery compared to control group. Both groups showed no haemodynamic variations. Conclusion: Current study showed that addition of Dexmedetomidine to Bupivacaine improves the quality of Supraclavicular Brachial plexus block in terms of prolonged duration of analgesia.